Missing the mountains or being the children of the sea (or not): A multi-method arts-based investigation - Mäkivuoti, Eija (2018)
The theme of the inquiry is to investigate, through a collaborative arts-based research investigation, how sense of belonging and not-belonging manifest among a group of migrating Faroese people through a storytelling process. In spring 2018, the artist-researcher collaborated with seven Faroese persons who have past or present experiences in living in Denmark. The thesis inquiry is a multi-method arts-based research investigation that utilises a method devised collaboratively through a guided auto-ethnographic inquiry in dialogue with the facilitating artist-researcher. The co-researchers engage in a 3-part-storytelling process through which they inquire their knowledge and lived experiences using a variety of expressive approaches. The collaborators share their lived experiences as people deriving from a small island nation situated in the midst of the North Atlantic Ocean, but also as people who are a part of the larger realm of the Danish Kingdom. The theoretical trajectories in the inquiry engage theories on representation and meaning-making, critical pedagogy, as well as collaborative and dialogic art practices, and as an undercurrent, postcolonial theories situated within the Nordic context. The theoretical trajectories provide a framework for critical self-reflection for the artist-researcher throughout the entire research process. This theoretical framework also raises essential ethical questions that inform how the collaboration between the artist-researcher and the collaborators is formulated and carried out. The theoretical trajectories lead towards an ethical approach in which the collaborating people are seen as co-creators of knowledge, as co-researchers and as the creators of their own narratives. In this collaborative research inquiry, the facilitating artist-researcher applies many roles and becomes for example a mentor, a curator and a sparring partner, who gently guides but does not direct, to keep the co-researchers engaged in a demanding 3-part storytelling process. In addition to the many ...